Considerations on the composition and spectra of the secondary radiation fields inside the E1 experimental area at ELI-NP. (December 2020) - Popovici, Maria – Ana; Vasilache, Radu A.
Abstract: At the new ultrahigh power laser facility ELI NP, experiments on the interaction of high power lasers and matter will be conducted. These experiments are expected to produce beams of highly energetic particles resulting in secondary radiation fields which will be highly complex and rather difficult to measure given their specifics (extremely short bursts, with time widths in the range of nanoseconds). The ELIFLUKA project was started to assess the doses in the areas surrounding the experimental halls, to evaluate the efficiency of the existing shielding solutions, to propose, if necessary, their optimization, and give optimal ways to monitor the radiation fields that might affect the facility personnel. The present paper is focused on the results concerning the composition and the spectra of the secondary radiation fields inside the E' experimental hall. A complex FLUKA geometry of the El area was built according to the real design of the experimental hall. With FLUKA we calculated the particle fluencies, the spatial distribution and spectra of each component of the radiation field, corresponding to two limit source terms, characterised by a thermal energy distribution with 40 MeV average and 250 MeV cut-off, and a second one with a flat energy distribution with 500 MeV average and 50 MeV FWHM. The FLUKA code was used to calculate all particle fluence spatial distribution inside the experimental hall, as well as the fluences and spectra for the main components of secondary radiation fields. These results can be used to design various experimental setups at E1 in such a way that the instruments would be positioned without risking significant activation and/or radiation damage and they provide a source term for the shielding calculations using the classical methods, as usually requested by the regulatory authorities.